MEMAHAMI LANDASAN PENDIDIKAN DALAM MENGOPTIMALKAN PROSES BELAJAR-MENGAJAR BAGI PENINGKATAN KUALITAS PENDIDIKAN - Disma, Dwi Ria Ibti; Aunurrahman, Aunurrahman; Halida, Halida; Sulistiyaningrum, Fitri (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Abstract This research aims to explore the foundations of education in an effort to optimize the teaching and learning process in order to improve the quality of education. Research methods involve literature analysis, interviews with experienced educators, and direct observation in educational settings. The research results highlight the importance of a deep understanding of the foundations of education as the main key in designing effective strategies to advance the quality of education. These findings provide valuable insights for the development of educational policy and the establishment of more effective teaching practices. In the discussion, the implications of the findings for improving the quality of education are discussed in depth, highlighting the challenges and opportunities that need to be considered by policy makers, educational practitioners and researchers in this field.